Determinan Akuntabilitas Pengelolaan Keuangan Desa Dengan Pemanfaatan Teknologi Informasi Sebagai Variabel Moderasi - Magdalena Nona Ice; Lilis Ardiani; Kurnia Kurnia (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to test and analyze the influence of competence, internal system control, and community participation on the accountability of village financial management, moderated by the use of information technology. The type of data used in the study was primary data obtained from questionnaires that were distributed directly to respondents, namely village heads, secretaries, treasurers, BPD, and communities within the Sikka Regency village government. Sampling through Purposive sampling and obtained a sample of 150 respondents. Data analysis was processed using SPSS through a statistical method of multiple regression with a moderation approach, namely Moderated Regression Analysis (MRA). The results of the analysis show that competence and internal control systems have a positive and significant effect, while community participation does not affect the accountability of village financial management. The use of information technology does not moderate the influence of competence, internal system control, and community participation on the accountability of village financial management. The implications of this research, especially for village officials in Sikka Regency, are expected to be better in accountability for managing villages finances, provide input to the Sikka district, so that in the future the village financial system application can be fully used in this area and can simplifying the village bookkeeping and spending system. In addtion, village officials are also expected to be able to involve the village community in all decision-making related to the interests and prodress of the village and society in general